Field performance of vegetative and seed propagated plants of coffee (Coffea arabica L.) - Carvalho, Mychelle; Jesus, Adriana Madeira Santos; Carvalho, Samuel Pereira de; Gomes, Carlos Nick; Soares, Ângela Maria (Coffee Science - ISSN 1984-3909, 2008)
Cutting is an alternative method for vegetative propagation of Coffea arabica L. hybrids for commercial purpose. However, the use of such method requires the understanding of the plant growth characteristics under filed conditions. Thus, the objective of the present study was to evaluate and compare the vegetative growth and first yield of Coffea arabica cv. Acaiá plants obtained by cuttings and with seed propagated plants. The experiment was installed in the year 2003 and carried out in the Department of Agriculture at Federal University of Lavras-UFLA. For cutting propagation, stems were treated with three concentrations (0, 2000 e 4000 mg.L-1) of Indol butiric acid (AIB), in the presence or absence of supplemental warming. The development and growth of the cuttings were compared to the plantlets obtained by traditional seed propagation. A randomized blocks design, with six plants per plot, considering four useful plants and three replications was used. The vegetative growth, height, and yield of the plants of coffee obtained from cutting and treated with 2000 mg.L-1 AIB, were significantly greater than those not treated. Also, the production of plagiotropic branches by the plants originated from cuttings was greater than those originated from seeds.